Synthesis of an Anticorrosive Pigment by Thermal Treatment of Iron Oxides from Steel Industry Wastes - Colpas-Ruiz, María Angélica; Gnecco-Molina, Camilo; Jiménez-Rodríguez, Gabriel Antonio; Pérez-Mendoza, José Andrés; Higuera-Cobos, Óscar Fabián (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This work reports the obtaining of an anticorrosive pigment composed mainly of hematite (ɑ-Fe2O3) from a powder steel industry waste from rust scale of rebar steel. This residue is mainly composed of Fe2O3 (87.97 %), SiO2 (6.13 %), CaO (1.88 %), Al2O3 (1.30%) and MnO (0.77 %). The total iron oxide of the residue is constituted by the following crystalline phases: magnetite, maghemita, lepidocrocita, wüstite, goethite and hematite. The production of a pigment with a high content of hematite was possible thanks to the high content of precursor iron oxides, which were calcined at different temperatures (750-850 °C) and holding times (0.5-1.50 h). For characterizing the iron content chemically and to identify their iron oxides phases, it was used X-ray fluorescence (XRF) and X-ray diffraction (XRD). The results showed that the pigment with the highest amount of hematite (ɑ-Fe2O3) was obtained at a calcination temperature of 850 °C and a holding time of 1.00 h.